Role of topical mupirocin ointment as a prophylaxis in catheter related infection in haemodialysis patients - Daud, Kamaliah Mohd; Salleh, Mohd Zaki; Amar, Azeril Haris Yafee (1999)
Central venous catheterization (CVC) is a common technique to establish rapid and temporary access for the delivery of haemodialysis in patients with renal failure. However its usage also carry tremendous problems such as infection, sepsis and even death. CVC is a known risk factor for Staphylococcus infection and bacteraemia. Mupirocin is a naturally occurring antibiotic which is active against Staphylococcus aureus including methicillin resistant and beta lactamase producing strains.A randomized prospective trial was conducted to assess the role of mupirocin ointment as a prophylaxis in catheter related infection in 28 haemodialysis patients. Of these 13 received skin disinfection at CVC insertion site with povidone iodine (control group) and 15 received the same treatment followed by topical application of 2% mupirocin ointment at the cannula site immediately following catheter placement and at the end of each dialysis session. Patients were followed up until catheter removal and were monitored for the development of catheter related infectiol) ( CRI). The proportion of CRI in mupirocin group was significantly lower than control (6.7%vs.38.4%,P<0.05).Staphylococcus aureus and l\1RSA bacteraemia was observed in 4 patients (30.7%) in control group and 3 of them died related to sepsis. None of these was observed in the mupirocin group. The hazard ratio of developing catheter related infection was 7.7 times greater in patients not receiving mupirocin. As a conclusion, topical mupirocin application at the catheter exit site significantly reduced the risk of catheter related infection especially Staphylococcus aureus septicaemia in haemodialysis patients.